Why is the book on the table?: um estudo sobre a constituição identitária de professoras de língua Inglesa em formação - Velasques, Matheus Trindade (2013)
This dissertation presents a study about the process of identity constitution of English as a Second Language (ESL) training teachers based on their oral narratives. The aim of this research was to study the oral narratives of five training teachers of ESL in the sixth semester of an English-Portuguese Teaching and respective Literatures Degree to identify which discourses and representations of what it is to be an ESL teacher constitute their teaching identities and from what social instances they come from. In order to achieve this goal, the memories of the subjects of this study about the English teachers they had during their mainstreaming schools and English language courses learning experiences, as well as of their first experiences in the classroom in the role of teachers, along with their representations of teacher's position in society were reconstructed in the format of oral narratives produced through the guidance of a semi-structured interview. This study is located at the borders between Applied Linguistics, specifically from the bias that Pennycook (2006) calls transgressive Applied Linguistics, and Cultural Studies in Education. For analysis purposes, we use specific concepts for narrative (MOITA LOPES, 2001; LARROSA, 1996), representation (WOODWARD, 2011, HALL, 1997c) and identity (Hall, 1997b; WOODWARD, 2011; SILVA, 2011). The study has identified the fluid and hybrid character of the training teachers identities which have been constructed by discourses coming from their experiences at mainstream schools, English language courses, ongoing training at the undergraduate course disciplines and their own professional experience, according to what was possible to map out in their interviews. The (positive and negative) examples of the teachers who have been part of their school lives are strong subjective force elements alongside their professional experiences. The narratives about their teaching styles enable the interpretation of the hybrid character of their professional identities, in which elements of their student, family and researcher identities mingle during the interview. The teachers seem to create a picture of the ideal teacher, the "good" teacher, which is set as a target domain and is linked to the formal aspects and use of English, pedagogical knowledge and good relationship with students, based on their experiences with ESL learning and teaching. These elements mentioned above seem to be fundamental in the identity construction of the ESL teachers in training analysed in this study.